CHARACTERISTICS AND CONSUMPTION OF FUEL OIL SOLAR OIL WITH HAZELNUT OIL IN DIESEL MOTOR - Muhammad Nurtanto; Sulaeman Deni Ramdani; Soffan Nurhaji (Universitas Sultan Ageng Tirtayasa, 2017)
This study aims to determine the characteristics of fuel (diesel oil, walnut oil and sesame oil), the characteristics of the fuel mixture and knowing the amount of fuel consumption with a variation of the engine rotation. Measurements were made using 898 analyzer stages. Data were analyzed descriptively by describing the graphics and measurable phenomenon. The test results found that: (1) the characteristics of hazelnut oil, sesame oil meets the characteristics of the fuel; (2) a mixture of diesel fuel to 80% with 10% of hazelnut oil and sesame oil 10% yield better characteristics; and (3) the fuel consumption of the engine rev 1600 rpm, 2000 rpm and 2300 rpm is more stable on a mixture of diesel fuel to 80% with hazelnut oil 10% and sesame oil 10% each SFC obtained as follows 0.279882, 0.288938 and 0.281213.